Influence of coastal upwelling on the fishery of small pelagics off Kerala, south-west coast of India - U. MANJUSHA, J. JAYASANKAR, R. REMYA, T. V. AMBROSE AND E. VIVEKANANDAN (Indian J. Fish., 2013)
In order to evaluate the impact of the interannual changes of upwelling on the small pelagics, the average chlorophyll a concentrations were compared with the fishery. The catch of small pelagics, especially that of the oilsardine increased from 1, 554 t in 1994 to 2,50, 469 t in 2007 in the Malabar upwelling zone off Kerala, India. The coastal upwelling index (CUI) during south-west monsoon increased by nearly 50% during the period 1998 to 2007. This substantial increase in coastal upwelling index elevated chlorophyll a concentration during monsoon which resulted in an increase of over 200% in annual average chlorophyll a concentration. The increasing coastal upwelling index and chlorophyll a during monsoon sustained an increasing catch of oilsardine during postmonsoon season. The responses of lesser sardine and Indian mackerel, which are midlevel carnivores, were different. The population increases of the oilsardine appear to replace decreases in the lesser sardines and Indian mackerel during the postmonsoon season.